Metastatic Osseous Pain Control: Radiation Therapy - Kang, Josephine; Formenti, Silvia C. (Seminars in Interventional Radiology, 2017)
Metastatic disease to the bone is a common manifestation of advanced cancer, and can result in pain, pathologic fractures, hypercalcemia, and overall functional compromise. External beam radiation is a proven, highly efficacious, and noninvasive therapy that can provide symptomatic relief from painful osseous lesions. When deciding upon the best treatment regimen, it is important to consider patient factors such as overall life expectancy, performance status, disease burden, and site of osseous metastatic pain. Determination of best treatment ideally requires multidisciplinary input from radiologists, medical oncologists, surgeons, pain management, and palliative care specialists together with radiation oncologists.
Keywords: palliative; radiation therapy; bone metastasis; interventional radiology